2007
DOI: 10.1007/s10897-007-9086-3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Expectations of Women Undergoing Cancer Genetic Risk Assessment: A Qualitative Analysis of Free‐Text Questionnaire Comments

Abstract: Individuals undergoing cancer genetic risk assessment have been found to have a poor understanding of the process, which may affect how well they cope with learning their risk. This paper reports free-text data from questionnaires completed by women undergoing a randomised controlled trial of a psychological intervention. Of the 268 women undergoing genetic assessment for familial breast/ovarian cancer risk who were invited to take part in the trial, 157 women returned research questionnaires. Of these, 97 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 41 publications
2
35
1
1
Order By: Relevance
“…This has been seen several times before in BRCA families (Phelps et al, 2007;Speice et al, 2002) and in families with HD or FAP (Sobel and Cowan, 2000;Sobel and Cowan., 2003;Duncan et al, 2008). Specifically, the current study highlights that individuals who are the only ones in their family to test positive may be especially at risk of feeling isolated since their family may not be able to empathize and provide the support needed.…”
Section: Theme # 3: Feeling More or Less Connected To Family Membersmentioning
confidence: 70%
See 3 more Smart Citations
“…This has been seen several times before in BRCA families (Phelps et al, 2007;Speice et al, 2002) and in families with HD or FAP (Sobel and Cowan, 2000;Sobel and Cowan., 2003;Duncan et al, 2008). Specifically, the current study highlights that individuals who are the only ones in their family to test positive may be especially at risk of feeling isolated since their family may not be able to empathize and provide the support needed.…”
Section: Theme # 3: Feeling More or Less Connected To Family Membersmentioning
confidence: 70%
“…As outlined in the Background and Significance section, previous studies have shown that individuals often decide to undergo BRCA testing to provide information for their family, some even feeling that their family has a right to know this information (Hallowell, 1999;Tercyak et al, 2007;Phelps et al, 2007;Foster et al, 2004;Daly et al, 2001;Goelen et al, 1999;Foster et al, 2002;Hallowell et al, 2003;Green et al, 1997). Thus, it was not surprising that index cases in the current study tended to feel an obligation or responsibility to inform their relatives of their BRCA mutation.…”
Section: Study Findings In the Context Of Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinician who wishes to help their patient grapple with these issues at a deeper level could consider a risk communication strategy that incorporates exploring: 1) their patient's existing estimates of numeric probability for a child to develop a psychotic illness, as well as 2) how their patient would describe the risk, 3) the factors that have contributed to this perception (for example, the presence of multiple additional affected family members), and 4) their patient's perceptions of illness severity, before attempting to provide any new information (Skirton and Eiser, 2003). Further, after the delivery of information about chances for children to be affected, the clinician could encourage the patient to reflect on the information in light of their previous perceptions, and its effect on their perceptions, such that unanticipated reactions can be addressed (Phelps et al, 2007).…”
Section: Risk Perception Differences Between Affected Individuals Andmentioning
confidence: 99%